Analysis of Managerial Procedures for Developing the Cambridge Curriculum in Junior High Schools - Lestari, Indah Beti; Wahyudin, Dinn; Dewi, Laksmi (Universitas Negeri Semarang, 2023)
This research aims to establish the managerial practices for designing the Cambridge curriculum at SMPS Golden Christian School Palangka Raya. This is a descriptive study with a qualitative methodology. The data source in this study came from in-depth interviews conducted with teaching staff at SMPS Golden Christian School Palangka Raya. The data analysis technique used is the descriptive, evaluative technique. The research results show three curriculum management procedures at SMPS Golden Christian School (GCS): planning, implementation, and evaluation. Henceforth, it is suggested that organizational management is also carried out to manage the scope, sequence of materials, continuity, balance, and integration so that the current curriculum can be organized and patterned. Abstrak Penelitian ini bertujuan untuk mengetahui prosedur manajerial pengembangan kurikulum Cambridge di SMPS Golden Christian School Palangka Raya. Jenis penelitian ini adalah penelitian deskriptif dengan menggunakan pendekatan kualitatif. Sumber data dalam penelitian ini berasal dari wawancara secara mendalam yang dilakukan dengan tenaga pengajar di SMPS Golden Christian School Palangka Raya. Teknik analisis data yang digunakan adalah teknik deskriptif evaluatif. Hasil penelitian menunjukkan ada tiga prosedur manajemen kurikulum yang dilakukan di SMPS Golden Christian School (GCS) yaitu manajemen perencanaan, manajemen pelaksanaan, dan manajemen evaluasi. Untuk selanjutnya, diberikan saran agar dilakukan pula manajemen organisasi untuk menata kelola terkait ruang lingkup, urutan bahan, kontinuitas, keseimbangan, dan keterpaduan agar kurikulum yang berjalan dapat terorganisir dan berpola.